A single centre 10-year experience of Mitrofanoffs procedure for varied indications with its outcome - Athawale, Hemangi R.; Mane, Shivaji B.; Vagheriya, Natasha; Kotawala, Hussain; More, Prathamesh; Daginawala, Taha (International Journal of Contemporary Pediatrics, 2020)
Background: To evaluate long term efficacy and complications of Mitrofanoffs procedure in patients with bladder dysfunction. Methods: Authors retrospectively reviewed the medical records of 51 patients who underwent construction of a continent catherisable channel (mitrofanoffs and monti) from 2009 till 2019 in our institution. Clinical findings and investigations result along with surgical techniques used were noted for these patients. Postoperative complications along with urinary continence and renal outcome were evaluated. Results: Mean age was 7 years and mean follow up was for 3 years. 27 patients were with neurogenic bladder and 24 with non-neurogenic bladder. The most common type of conduit was appendicovesicostomy (38) followed by illeal monti (12) and ureter (1). The most common stomal site was umbilicus (44) followed by right lower abdominal quadrant (6). Catherterizable conduit complications included stomal leakage in 3, mucosal prolapse at the stoma site in1 and an intra peritoneal leak requiring exploratory laprotomy and revision in1. Relative stomal continence was achieved in 98%. The preoperative serum creatinine & blood urea nitrogen (BUN) at the time of mitrofanoffs procedure at the last follow up after the procedure were sought and compared using Chi square test showed statistically significant improvement (p<0.01). No differences in outcome and complication rates were noted between different types of conduit, sites of implantation, or segments used for augmentation. Conclusions: Mitrofanoff is a safe and reliable procedure in children who are dependent on intermittent catherisation in developing countries. Appendicovesicostomy is our first option followed by yang -monti illeovesicostomy. While stomal continence is excellent patient education, family motivation and cost reduction are important factors for its lasting efficiency.